IDENTIFIKASI MORFOMETRIKS DAN JARAK GENETIK AYAM KAMPUNG (domesticated chicken) DI KABUPATEN BATUBARA - Rhyndhyra Hummairah (Jurnal Peternakan Integratif, 2015)
ABSTRACT                This study aims to identify the main feature size and shape of the morphometrics and the genetic distance of local chickens in various districts of Batubara. This research used survey method with 2392 number of sample of chicken and data were analized with software SAS (Statistics Analytical System) which is used as a measure of genetic distance Mahalanobis genetic distance squared minimum, and Software MEGA6  for get Phenogram tree with UPGMA method ( Unweight Pair Group Method with Arithmetic ). The results based morphometric analysis showed differences in morphology on every chicken.  Based on the similarities and mix in between district and genetic distance from chicken. According to morphometric analysis, there is morphological different on every local chicken from 7 existed district in Batubara that Sei Suka and Sei Balai ( 1.26 ), Air Putih and Talawi ( 3.79 ), Medang Deras and Tanjung Tiram ( 1.73 ) and Lima Puluh (2.13 ). Conclusions showed that primary identified that appears are the length of tibia, metatarsus width and length beak , and the genetic distance of 7 districts there is one distinct districts namely at Lima Puluh (2.13), while six other districts were similarities between the two districts . Keywords : Morfometriks , Genetic distance , Kampung Chicken, Batubara.